EFFORTS MADE BY POLRI AS LAW ENFORCEMENT OFFICIALS IN COMMITTING CRIME WITH VIOLENCE (BEGAL) - Hermawan Sutanto; Syahrul Borman (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
The crime of robbery involves theft that can lead to the loss of a person's life. To address this issue, the police are empowered with authority and responsibilities outlined in Article 13 of Law Number 2 of 2002. These responsibilities include maintaining security and public order, upholding the law, and providing protection, services, and assistance to the community. This research aims to (1) understand the role of the National Police in combating criminal acts involving violence (such as "begal"), and (2) explore efforts to uphold the rule of law when addressing such criminal acts. This study adopts a normative legal research approach, incorporating statutory, case-based, and conceptual legal analyses. Legal materials are examined through interpretation and relevant legal theories, leading to deductive conclusions. The findings of this study reveal that (1) Robbery is classified as a criminal act punishable under Criminal Code Articles 365 and 368. The National Police employs preventive measures by advising the public to exercise caution in areas susceptible to robberies. Additionally, repressive legal actions are taken through investigations and trials to administer punishments. (2) If certain conditions for accountability are met, an individual displaying deviant behavior may commit specific criminal acts. Therefore, a perpetrator utilizing a planned approach to commit robbery, accompanied by the required evidence, could be sentenced to up to 12 years of imprisonment.